2022
DOI: 10.1017/wet.2022.31
|View full text |Cite
|
Sign up to set email alerts
|

Surveying stakeholder’s perception of glufosinate and use in North Carolina

Abstract: Glufosinate is among the few remaining effective herbicides for postemergence weed control in North Carolina crops. The evolution of glufosinate resistance in key weeds is currently not widespread in North Carolina but to better assess the current status of glufosinate effectiveness, surveys were distributed at extension meetings in 2019 and 2020. The surveys were designed to provide information about North Carolina farmers’ perception of and use of glufosinate. Many North Carolina farmers (≥26%) apply glufosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Although sequential applications of glufosinate ceased or decreased Palmer amaranth seed production, these applications should be recommended to farmers with caution to reduce the selection pressure on Palmer amaranth evolving resistance to glufosinate. Sequential applications of glufosinate are common in North Carolina row crops and many North Carolina farmers utilize additional tactics for herbicide resistance management (Jones et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sequential applications of glufosinate ceased or decreased Palmer amaranth seed production, these applications should be recommended to farmers with caution to reduce the selection pressure on Palmer amaranth evolving resistance to glufosinate. Sequential applications of glufosinate are common in North Carolina row crops and many North Carolina farmers utilize additional tactics for herbicide resistance management (Jones et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Glufosinate was applied at three timings when Palmer amaranth was 5 (early postemergence), 7–10 (mid postemergence), and 10–20 cm tall (late postemergence), and all orthogonal combinations of those timings (Table 1). The glufosinate application timings were selected to represent how North Carolina farmers are currently using the herbicide (Jones et al., 2022). A nontreated check was included in the experiment as well.…”
Section: Methodsmentioning
confidence: 99%
“…States, where glufosinate is applied extensively and intensively (Jones, Cahoon, et al, 2022;Riar et al, 2013). Although glufosinate is efficacious on most weeds elsewhere, continued sole reliance will select for more glufosinate-resistant weeds (Owen & Zelaya, 2005;Schwartz-Lazaro et al, 2018;Shergill et al, 2018;Shyam et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation occurs with common ragweed, ivyleaf morningglory, and sicklepod, which are also pervasive and hard-to-control weeds in the southeastern United States (Jones et al 2022;Van Wychen 2017;Webster and Nichols 2012). Previous research has shown that dicamba and glufosinate are effective on these species; however, mixtures and sequential applications of these herbicides have not been evaluated (Everman et al 2007;Kalina et al 2021;Leon et al 2016;Schrage 2018).…”
Section: Introductionmentioning
confidence: 93%